Cell death mechanisms induced by gold nano-immunoconjugates-mediated photodynamic therapy against human oesophageal cancer stem cells - Didamson, Onyisi Christiana; Chandran, Rahul; Abrahamse, Heidi (Frontiers in Immunology, 2025)
BackgroundThe current conventional therapy for oesophageal cancer is unable to effectively eliminate oesophageal cancer cells as a result of cancer stem cells (CSCs). These CSCs are the main factors responsible for treatment failure and tumour relapse associated with the present conventional oesophageal cancer therapy. A nano-immunoconjugate-based photodynamic therapy (PDT) proposes a potential approach to eliminate these CSCs efficiently.MethodIn this study, we examined the mode of cell death action induced by the nano-immunoconjugates (NIC) mediated PDT comprising aluminium phthalocyanine tetra sulfonic acid chloride (AlPcS4Cl), gold nanoparticles (AuNPs), and anti-CD271 antibody (AlPcS4Cl-AuNPs-anti-CD271) against human oesophageal CSCs in vitro. The oesophageal CSCs were treated with NIC-mediated PDT, and their impacts on cell viability, oxidative stress, mitochondrial membrane, efflux of cytochrome c protein, caspase 3/7 activity, and cell death mechanism were examined. We further evaluated the effects of the treatment on the various phases of the cell cycle, DNA damage response pathways, and autophagy.ResultsFindings from this study showed that NIC-mediated PDT significantly inhibited the cell growth of oesophageal CSCs, promoted reactive oxygen species (ROS) production and mitochondrial-mediated apoptotic cell death through the alteration of mitochondrial membrane potential Δψm, high efflux of cytochrome c protein, high activity of caspase 3/7 protease, and early apoptosis. Moreover, NIC-mediated PDT triggered cell cycle checkpoint activity in the G0/G1 phase, stimulated DNA damage response by increased DNA double-strand breaks (DSB) and ATM (ataxia-telangiectasia mutated) upregulation, and activated an autophagy action.ConclusionThe outcomes from this study showed the anticancer efficiency of gold nano-immunoconjugate-based PDT against human oesophageal CSCs. Overall, this study provides a rationale for gold nano-immunoconjugate-based PDT for a promising therapeutic application in the clinical treatment of oesophageal cancer.